Populations and fate of faecal bacteria in contaminated water of the Eerste River below Stellenbosch - Rossouw, Jacques,1972- (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1999.